Application of Standard Agreements in Lease Purchase Contracts: Legal Implications of Business in the Realm of Civil Law - Delycia Anwar Rannu; Gunardi Lie (Syntax Idea, 1930)
Business practices provide easy access to capital for certain goods. Hire purchase arises when the buyer cannot afford to pay cash. Standard agreements cannot be negotiated by consumers. In Indonesia, this practice is growing rapidly, especially in the motorbike trade. The application of standard agreements has important implications in business law, such as consumer protection and dispute resolution. Research on this subject is important for identifying challenges and opportunities in modern business. This legal research uses a normative juridical approach, which is a research method that relies on secondary data sources, such as library materials. This normative juridical approach involves analysis of legal principles, legal systematics, as well as vertical and horizontal synchronization in the civil law system in Indonesia. The results of this research are that the research highlights the importance of understanding the business practices of hire purchase contracts, especially the application of standard agreements and their legal implications. This raises questions regarding the balance of rights and obligations between providers and recipients of goods or services. It is important to understand the legal framework to ensure equality of rights and obligations and maintain the principles of consumer protection and public order in this business practice